The Paradox of Coastal Modernization: Urban Transformation in Makassar’s Centre Point of Indonesia - Arifin, Ibrahim; Nur, Muhammad; Musdalifah, Musdalifah; Diki, Hendrawan; Mutmainnah M., Ulfah (Citra Media Publishing, 2025)
Coastal development has become a crucial discourse in studies of development and urbanization, revealing the tension between economic growth and social inequality. Many coastal cities in Southeast Asia, including Indonesia, have adopted land reclamation projects as strategies to strengthen their modern image and economic competitiveness. However, these projects often generate social displacement, ecological degradation, and the marginalization of local communities. This study aims to understand how coastal residents and visitors interpret spatial transformation, adapt to socio-economic changes, and negotiate their positions within the Centre Point of Indonesia (CPI) development project in Makassar. Employing a critical ethnographic approach, data were collected through field observations, in-depth interviews with residents and visitors, and analysis of online media reports. The findings reveal three major dynamics: the transformation of urban infrastructure and accessibility, the emergence of new, exclusive economies, and local communities’ social adaptation strategies to modernization. This study concludes that the CPI project embodies the paradox of coastal modernization, economic growth accompanied by the reproduction of spatial inequality, while contributing to theoretical debates in development sociology concerning spatial justice and local community participation in urban development practices in Indonesia.